Guide to operating systems security - Palmer, Michael J., 1948- (Australia : Thomson, 2004)
Guide to Operating Systems Security is designed to expand networking student's basic network and operating system skills to include planning, implementation, and auditing of a system's security. This text covers a variety of operating systems, including a Windows client operating system, Windows server operating system, Linux, Novell NetWare, and Mac OS. Each chapter offers extensive learning aids including review questions, hands-on projects, and case studies that reinforce concepts and help student apply them to real world applications.
Operating Systems Security: Keeping Computers and Networks Secure -- Viruses, Worms, and Malicious Software -- Security Through Authentication and Encryption -- Account-Based Security -- File, Directory, and Shared Resource Security -- Firewalls and Border Security -- Physical and Network Topology Security -- Wireless Security -- Web, Remote Access, and VPN Security -- E-Mail Security -- Security Through Disaster Recovery -- Security Through Monitoring and Auditing Appendix A: Operating System Command-Line Commands
Includes index.
1
Keywords: Operating systems (computers)